Publisher Correction: Non-specific interactions govern cytosolic diffusion of nanosized objects in mammalian cells. Issue 11 (November 2018) - Etoc, Fred; Balloul, Elie; Vicario, Chiara; Normanno, Davide; Liße, Domenik; Sittner, Assa; Piehler, Jacob; Dahan, Maxime; Coppey, Mathieu
In the version of this Article originally published, Supplementary Videos 3–5 were incorrectly labelled; 3 should have been 5, 4 should have been 3 and 5 should have been 4. This has now been corrected.